THEORETICAL FUNDAMENTALS OF CREATIVE ECONOMICS RESEARCH - PANOVA, Iryna; STEPENENKO, Victroria (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The economic well-being and power of a country depend on a number of factors, including the availability of natural resources, a favorable geographical location relative to world trade routes, and a developed industry. However, today one of the most promising areas for the state economy is the development of the creative economy. It, as a phenomenon, emerged in the late twentieth century, and the XXI - was the beginning of the development and expansion of the concept.The cultural and creative industries operate in a complex business environment, where they are defined by standard provisions relating to business, as well as intellectual property rights, taxation and many other issues. Thus, the regulatory framework should promote the artistic development, provision and regulation of entrepreneurial activity, while encouraging and preserving the cultural diversity of the whole of Europe, including Ukraine. The cultural sector is constantly changing, this revolutionary phenomenon is caused by changes in digital security. In response to these changes, the issue of regulating the concept of creative industries arises, and therefore governments are increasingly needing to assess and implement the regulatory framework. Thus, further sustainable development of the creative sector of the economy will have a positive impact on job creation, increase corporate profits, increase incomes, develop infrastructure, increase the tourist attractiveness of destinations, increase the flow of foreign tourists and more. In addition, much of the creative and intellectual resources around the world are invested in culture. Human creativity, innovations and ideas, both at the individual and social levels, are the key factors in the industry and the real wealth of the state today.
Keywords: creative economy; creative industries; creative environment; culture